Ocular adnexal lymphoma in Denmark: a nationwide study of 387 cases from 1980 to 2017. Issue 7 (30th July 2020) - Holm, Frederik; Mikkelsen, Lauge Hjorth; Kamper, Peter; Rasmussen, Peter Kristian; Larsen, Thomas Stauffer; Sjö, Lene Dissing; Heegaard, Steffen
Abstract : Background: Nationwide studies of ocular adnexal lymphoma (OAL) are very rare in the literature, and knowledge on incidence, subtype distribution and long-term survival data is limited. This is the largest national study of OAL to date. This study sought to find information on incidence, changes in incidence, clinical findings, distribution of subtypes, survival and prognostic factors. Methods: Patients diagnosed with OAL from January 1, 1980 to December 31, 2017 were identified in Danish registers, and clinical as well as survival data were collected. The data were analysed with Kaplan-Meier plots and log-rank test. Results: 387 patients were included in the study. The major lymphoma subtypes were extranodal marginal-zone B cell lymphoma (EMZL) (55%), diffuse large B cell lymphoma (DLBCL) (13%), mantle cell lymphoma (MCL) (11%) and follicular lymphoma (FL) (10%). OAL is a disease of the elderly (median age 69 years). The incidence of lymphoma of the ocular adnexal region has increased significantly throughout the time period of the study (Pearson correlation coefficient, r=0.65; P<0.001). In the period 1980–1984, the incidence was 0.086 per 100 000, which increased to 0.307 per 100 000 in the period 2013–2017. Low-grade, low-stage primary lymphomas were treated with radiotherapy, whereas patients with high-stage, high-grade and/or relapsed disease were treated with chemotherapy. Low-grade subtypes EMZL (89%) and FL (56%) had better 10-year disease-specific survival than the high-grade lymphomas DLBCL (38%) and MCL (31%)(p<0.001). Conclusion: OAL is increasing in incidence in the Danish population for unknown reasons. However, the prognosis for most OAL is favourable, as highlighted in this national long-term study.